Student preparedness for artificial intelligence-driven volatility, uncertainty, complexity, and ambiguity (VUCA) environments: Scale development and validation - Choudhury, Sourav; Beri, Nimisha; Chechi, Vijay Kumar; Sofal, Firdous Ahmad; Devi , Anukampa (Journal of International Students, 2026)
Technology has permeated the workplace, which demands new skills from the labor force. This is characterized by constant transformations and is known as the VUCA (Volatility, Uncertainty, Complexity and Ambiguity) world, with artificial intelligence (AI) being a key driver. This study aimed to develop a comprehensive scale to measure students’ preparedness to face AI-driven VUCA by integrating AI across the three dimensions of the 21st-century skill set as an attempt to fill the gap in the availability of such a tool. A quantitative research design was employed, with 626 students pursuing higher education sampled using a convenience sampling technique. The initial item pool consisted of 29 items drawn from an array of research articles. The content validity index, purification, exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were carried out on three dimensions. The validated final scale has 25 items, with a high reliability score of 0.882.